124k views
0 votes
Complete the square to transform the quadratic equation into the form (x – p)2 = q.

x2 - 6x - 8 = 6
A) (x - 6)2 = 9
B) (x - 3)2 = 23
C) (x - 6)2 = -9
D) (x - 3)2 = -23

User Nighliber
by
5.6k points

2 Answers

5 votes

Answer:

its B

Explanation:

USA Test Prep

User Artem Luzhanovskyi
by
6.6k points
1 vote

Answer: The correct option is (B)
(x-3)^2=23.

Step-by-step explanation: We are given to complete the square and transform the following quadratic equation in the form
(x-p)^2=q.


x^2-6x-8=6~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We have


x^2-6x-8=6\\\\\Rightarrow x^2-6x=6+8\\\\\Rightarrow x^2-6x=14\\\\\Rightarrow x^2-2* x* 3+3^2=14+3^2\\\\\Rightarrow (x-3)^2=14+9\\\\\Rightarrow (x-3)^2=23.

Thus, the required transformed form of given equation (i) is


(x-3)^2=23,

where p = 3 and q = 23.

Option (B) is CORRECT.

User Selman
by
5.9k points